2006
DOI: 10.1007/s10616-006-9033-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimized and efficient preparation of astrocyte cultures from rat spinal cord

Abstract: Astrocytes constitute a major class of glial cells in the CNS, and play crucial roles in physiological functioning, performance and maintenance of the CNS, as well as promotion of neuronal migration and maturation. Astrocytes have also been directly and indirectly implicated in the pathophysiology of various trauma occurrences, development of neurodegenerative diseases and nerve regeneration. To further understand mechanisms by which astrocytes elicit these effects, the first critical step in the study of astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The cultures were grown in DMEM containing 20% FCS, supplemented with 2 mM glutamine, 25 mM HEPES, 50 U/ml penicillin, and 50 lg/ml streptomycin at 37°C with 5% CO 2 . About 48-60 h in vitro later, purification of cell was undertaken according to previously protocol (Yang et al 2006).…”
Section: Preparation and Culture Of Astrocytesmentioning
confidence: 99%
“…The cultures were grown in DMEM containing 20% FCS, supplemented with 2 mM glutamine, 25 mM HEPES, 50 U/ml penicillin, and 50 lg/ml streptomycin at 37°C with 5% CO 2 . About 48-60 h in vitro later, purification of cell was undertaken according to previously protocol (Yang et al 2006).…”
Section: Preparation and Culture Of Astrocytesmentioning
confidence: 99%
“…Our interpretations of the results were given as follows: astrocytes had been cultured according to our previous study protocol (Yang et al 2006(Yang et al , 2009. And also these cells had been maintained and subcultured in culture medium containing serum over 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…Primary astrocyte culture, purification, and wound model were undertaken and processed according to previously described by Yang et al (2006Yang et al ( , 2009 in accordance with guidelines at the animal Care and Use committee of China. In this study, the purity of the astrocyte cultures was never below 98% as confirmed by anti-glial fibrillary acidic protein (GFAP).…”
Section: Culture Of Astrocytes and Wound Modelmentioning
confidence: 99%
“…It had no effect on her left leg, but her right leg swung a few times and stopped. It clearly proved that her right leg did have a mild ability to move [4][5][6][7].…”
Section: Early Neurosurgery Of Spinal Cord Contusionmentioning
confidence: 96%